Electrical tree degradation in high‐voltage cable insulation: progress and challenges. Issue 4 (1st August 2020) - Su, Jingang; Du, Boxue; Li, Jin; Li, Zhonglei
Abstract : High‐voltage direct current (HVDC) and high‐voltage alternating current (HVAC) cables are the most important equipment for high‐voltage, large‐capacity and long‐distance power transmission. Electrical tree is a pre‐breakdown phenomenon leading to failure of insulation materials, and it is the major issue that threatens the safe and stable operation of HVDC and HVAC cable systems. This study summarises and analyses the achievements in the research of electrical tree for HVDC and HVAC cables. The initiation mechanisms of the electrical tree, including Maxwell electro‐mechanical stress, charge injection–extraction, charge trapping and electroluminescence theories, are elaborated for fully understanding the electrical degradation process in insulation materials. Then, the influences of the high electric field, high temperature and mechanical stress on electrical tree behaviours are discussed, and the relationship between charge transport and the electrical tree is analysed and illustrated. The suppression methods of the electrical tree are put forward by introducing inorganic and organic additives into insulation materials, and the suppression mechanisms are presented from the viewpoints of the structure‐property and microscale–macroscale relationships. Recently, the electrical tree research studies are focused on the high‐precision of initiation models, high‐dependence of multi‐physical fields and high‐efficiency of suppression methods. The achievements provide theoretical support for improving the electrical performance of insulation materials, while it is a practical problem to explore their application feasibility in HVDC and HVAC cable.